Novel mobile agent dynamic data integrity protection protocol - LI Peng-fei1; QING Si-han2; MA Heng-tai1; DENG Yong1 (Tongxin xuebao, 2007)
Integrity characteristics of dynamic data was redefined and classified by attacker capability,and then it was analyzed how to protect truncation attack with collusion.After that,a data protection protocol of free-roaming agent was presented.The protocol used a reverse chained signature to protect the integrity of roaming path,and protected the dy-namic data integrity based on this.Specially,the protocol provided truncation resilience in collusion condition,and its secure property was proved by formal method.